1990
DOI: 10.1113/jphysiol.1990.sp018244
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine is not essential for exercise hyperaemia in the hindlimb in conscious dogs.

Abstract: SUMMARY1. The contribution of endogenous adenosine to the increase in hindlimb blood flow that occurs during treadmill exercise was evaluated in conscious dogs. We postulated that if adenosine is essential for the hindlimb hyperaemic response, then pharmacological treatment of the animals with adenosine receptor antagonists should decrease hindlimb blood flow during treadmill exercise.2. A total of twenty-three dogs were chronically instrumented for measurement of aortic blood pressure and hindlimb blood flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Moreover, adenosine receptor blockade with aminophylline (non‐selective) and 8‐phenyltheophylline during voluntary treadmill exercise supports (Metting et al. 1986) as well as rejects (Koch et al. 1990) a role of adenosine for exercise‐induced hyperaemia.…”
Section: Role Of Adenosine In Skeletal Muscle Vasodilationmentioning
confidence: 99%
“…Moreover, adenosine receptor blockade with aminophylline (non‐selective) and 8‐phenyltheophylline during voluntary treadmill exercise supports (Metting et al. 1986) as well as rejects (Koch et al. 1990) a role of adenosine for exercise‐induced hyperaemia.…”
Section: Role Of Adenosine In Skeletal Muscle Vasodilationmentioning
confidence: 99%
“…In contrast, other studies failed to show any increase in venous Ado concentration (1, 39) or skeletal muscle Ado content (28). Furthermore, infusion of Ado receptor antagonists resulted in reduction of exercise hyperemia in some animal experiments (22, 27,29,38), whereas other studies found no reduction of exercise hyperemia (14,17).…”
mentioning
confidence: 97%
“…In contrast, other studies failed to show any increase in venous Ado concentration (1, 39) or skeletal muscle Ado content (28). Furthermore, infusion of Ado receptor antagonists resulted in reduction of exercise hyperemia in some animal experiments (22, 27,29,38), whereas other studies found no reduction of exercise hyperemia (14,17).Although there are limited human studies regarding the role of Ado in exercise hyperemia, recent studies have suggested a likely contribution of Ado to exercise hyperemia by demonstrating 1) a direct linear relationship between interstitial concentration of Ado and femoral artery blood flow during dynamic one-legged knee extension exercise (13,20); 2) localization of vasodilating Ado A 1 , A 2A , and A 2B receptors on human vascular smooth muscle cells and vascular endothelial cells (21); and 3) that Ado infusion into the femoral artery caused increases in blood flow comparable to hyperemic levels during exercise (31). These latter authors also found that theophylline (Ado receptor antagonist) infusion during exercise decreased femoral arterial blood flow by 20%, suggesting an important role for Ado in human exercise hyperemia.…”
mentioning
confidence: 99%
“…In addition, adenosine acts on presynaptic receptors to inhibit sympathetic nerve-mediated vasoconstriction (Fuglsang and Crone, 1987). However, in studies of canine gracilis muscle, it was concluded that, although released adenosine could contribute to exercise hyperemia, it is likely not to be the main factor, particularly in the initial stage (Ballard et al, 1987;Koch et al, 1990). Adenosine, acting via A 2A receptors, contributes up to 30% of the functional hyperemic response in the hindlimb of anesthetized cats (Poucher, 1996).…”
Section: Skeletal Muscle Microvasculature and Femoral Arterymentioning
confidence: 99%